XV. Orszagos keramia biennale : pécs, 1998. - Jozsef, Sarkany; Pécsi Galéria, Pécs; Hongaarse keramiek biennale Pécs 1998 (Pécs : Janus Pannonius Museum, 1998)
Albrecht, Julia ; Antal, Andras ; Balazs, Peter ; Balog, Anita ; Bedecs, Monika ; Benedek, Olga ; Berczy, Katalin ; Boda, Peter ; Czebe, Istvan ; Dios, Gabriella ; et al.
XV. Orszagos Keramia Biennale, Pécsi Galéria, Pécs, 1998. julius 5. - augusztus 24.
kunstcatalogus
Keywords: Jozsef Sarkany